The Forgotten Rights of the Physician and the Forgotten Obligations of the Patient (in the Doctor-Patient Relationship) - Riofrio, Juan Carlos (2024)
The present work fills a frequent gap in bioethical literature, which tends to be more focused on patient rights (especially autonomy) and physician duties. From a more interpersonal, bioethical, and legal perspective, this work highlights the forgotten aspects of the doctor-patient relationship to balance the positions of the parties. For this purpose, following a historical introduction, the human significance of the doctor-patient relationship is examined. This is then compared with a list of human rights and ethical-legal standards (taken from another work), as well as with some current regulations. In this way, the main rights of the doctor and the duties of the patient are systematically analyzed. This new approach highlights some forgotten aspects of this relationship, such as: the patient’s primary duty to take care of themselves, their duty to collaborate with medical work, and their duty of gratitude to medical staff, as well as the physician’s right to rest, to adopt certain security measures, to object to treatments they consider immoral or unproportional, to freedom of expression, and to dialogue on equal terms with other professions.